Evaluations of the apparent activation energy distribution function for the non-isothermal reduction of nickel oxide nano-powders - Janković, Bojan Ž.; Janković, Marija M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The differential conversion curves of the non-isothermal NiO reduction process by hydrogen are fitted by the Weibull (non-isothermal) probability density function (Wpdf), in a wide range of the degree of conversion (α = 0.06 - 0.96). It was established that the Weibull distribution parameters (β and η) show the different dependences on the heating rate of the system (vh) (shape parameter (β) – linear form and scale parameter (η) – exponential form). Model independent values of the apparent activation energy were calculated using the Friedman’s isoconversional method. It was found that the calculated apparent activation energy depends on the degree of conversion, α, and it shows a constant value in the range of the degree of conversion 0.20 ≤ α ≤ 0.60 (Ea = 90.8 kJ mol-1). Knowing the Weibull distribution function of reaction times, it is possible to determine the density distribution function of apparent activation energies at different heating rates. It was established that the changes of the symmetry of density distribution functions may be an indication for deviations from the simple crystallization kinetics as expressed by the Johnson-Mehl-Avrami (JMA) model, and this behaviour is probably due to a more complex transformation process such as a process described by the two-parameter autocatalytic Šesták-Berggren model.